Cross-calibration of human PET scanners with phantom studies - Hällilä, Johanna (My University, 2023)
In the field of medical imaging currently, the speed of the technological advancements in camera design, characteristics, and performance between the Positron Emission Tomography (PET) systems varies considerably. The evaluation of image quality attributes is one way to compare the differences. The target organisation assigned the work needs to understand the differences in camera performance in the generational change of medical imaging devices to support long-term research programs. The thesis compares the performance and image quality of two different PET cameras. The study aims to compare the PET High-Resolution Research Tomograph (HRRT) concept camera’s image quality to the Siemens Biograph Vision Quadra Positron Emission Tomography/Computer Tomography (PET/CT) camera. As an outcome of image quality analysis, it is expected to determine, if the images are comparable between the different cameras. The study has been carried out with phantom studies, using a phantom which is filled using one of the most common PET-tracers, Fluorine 18 Fluorodeoxyglucose. The data received from the imaging of the phantom is analysed using different data tools (such as Carimas, Python, MATLAB, and Excel) with selected statistical methodologies common in medical image analysis. During the process, the research is documented for further studies. The result is an accuracy comparison that can be used to understand how similar or different the images are from the PET cameras. This study has raised awareness of the HRRT concept camera and Siemens Biograph Vision Quadra PET/CT camera and the differences that resulted from the data comparison. The process has been documented and presented as a summarised process for continued similar research. The performed work details are available for repetition to expand the image analysis for different data sets and devices. The research concerning the overall study and devices is novel in its field. The successful measurements, data extraction, and analysis have provided a basic understanding with recommendations for future research.
Keywords: PET, PET/CT, PET cameras, medical imaging, image analysis